KEEFEKTIFAN MODEL PEMBELAJARAN KOOPERATIF TIPE CONCEPT SENTENCE BERBANTUAN MEDIA ROLL THE CAN TERHADAP KETERAMPILAN BERPIKIR KREATIF DALAM MENULIS KARANGAN NARASI - Novianti Novianti; Eko Fajar Suryaningrat (Bale Aksara: Jurnal Pendidikan Sekolah Dasar, 2020)
This research was done for to find out the effectiveness of cooperative learning model type concept sentence helps the media roll the can in learning writing a narrative. The purpose of this study was to find the effectiveness and difference of cooperative learning model type concept sentence helps the media roll the can in improving creative thinking skills in writing narrative between the use of cooperative sentence model type concept sentence helps the media roll the can with conventional model. The research method used in this study is the experimental method. Reseacrh done, that is (1) cooperative learning model type concept sentence helps the media roll the can is effective in learning the creative thinking skills in writing narrative with average pretest of 35,2 while the average posttest is 49.3 higher than the control class. In the control class the average score pretest 30.5 while the posttest average 37.3 is still lower than the experimental class. (2) there is a difference in creative thinking skills in writing narrative by using cooperative learning model type concept sentence helps the media roll the can with conventional models. The results of the independent samples t-test on the posstest value indicate the value of sig. (2-tailed) of 0.00 (p<0.05). The conclusion of this study is the cooperative learning model type concept sentence heps the media roll the can improve creative thinking skills in writing narrative.